Penerapan Pijat Oketani Pada Ny. S Untuk Mengatasi Menyusui Tidak Efektif - Rahayu, Irna Fitriana; Rohmayanti, Rohmayanti; Rahayu, Heni Setyowati Esti (Universitas Muhammadiyah Magelang, 2023)
Abstract Introduction Introduction:mother’s milk is the fist and ideal natural food needed for babies, especially in the first months of a baby’s life. The World Health Organization (WHO) recommends giving exclusive breastfeeding to babies without additional food for as long as the baby is 6 monts old and then continuing breastfeeding until the baby is the first two years of life. Breast milk contains all the elements of nutrients that have benefits as nutrients, hormones, immunity, growth factors, antiallergy, antibodies,and inflammation that can prevent infection in babies. Objective: this study aims to apply oketani massage to overcome the problem of ineffective breastfeeding in nursing mothers. Method:the research method uses a case study with a consecutive sampling technique on a spontaneous post partum mother on the third day who experienced breast milk problems that were not smooth, the baby was unable to attach to the mother’s breast and the milk is not dripping or gushing. Participant given the application of oketani massage. This research conducted in Sumberarum Village, Tempuran, Magelang Regency on May 2023. Results:the results of the study on post partum mothers after the oketani massage was carried out, the problem of breastfeeding was not effectively resolved with the criteria for increased milk dripping / emission, increased adequate milk supply, increased mother's self-confidence, decreased anxiety or worry, and baby's BAK more than 8 times within a day, the blisters on the nipples have decreased, the baby's crying while feeding has decreased, the baby's sucking has not continuously decreased. Conclusion:the application of oketani message can overcome the problem of ineffective breastfeeding in primiparous post partum mothers. Keywords: breast milk; back rolling massage: post partum mother. Abstrak Latar Belakang;Air Susu Ibu (ASI) merupakan suatu makanan alamiah yang pertama dan ideal yang dibutuhkan untuk bayi terutama pada bulan-bulan pertama kehidupan bayi. World Health Organization (WHO) merekomendasikan pemberian ASI eksklusif pada bayi tanpa makanan tambahan selama bayi berusia 6 bulan kemudian dilanjutkan pemberian ASI sampai bayi berusia dua tahun pertama. ASI mengandung semua unsur zat gizi yang mempunyai manfaat sebagai nutrisi, hormon, kekebalan tubuh, faktor pertumbuhan, anti alergi, antibodi, serta inflamasi yang dapat mencegah terjadinya infeksi pada bayi. Tujuan:penelitian ini bertujuan menerapkan pijat oketani untuk mengatasi masalah ketidakefektifan menyusui pada ibu menyusui. Metode:metode penelitian menggunakan studi kasus dengan teknik pengambilan sampel secara konsekutif pada ibu post partum spontan pada hari ketiga yang mengalami masalah ASI tidak lancar, bayi tidak dapat melekat pada payudara ibu dan ASI tidak menetes, atau memancar. Peserta diberikan penerapan pijat oketani. Penelitian ini dilakukan di Desa Sumberarum, Tempuran, Kabupaten Magelang pada bulan Mei 2023. Hasil:hasil penelitian pada ibu post partum setelah dilakukan pijat oketani, masalah menyusui tidak teratasi secara efektif dengan kriteria peningkatan keluar/tetesan ASI, peningkatan suplai ASI yang adekuat, kepercayaan diri ibu meningkat, kecemasan atau kekhawatiran berkurang, dan BAK bayi lebih dari 8 kali dalam sehari, lecet pada puting sudah berkurang, bayi menangis saat menyusu berkurang, isapan bayi tidak berkurang terus-menerus. Kesimpulan: penerapan pijat oketani dapat mengatasi masalah menyusui tidak efektif pada ibu post partum primipara.